Determination of 5‑hydroxymethylfurfural in aged Malaysian Tualang honey and its effects on the female reproductive system of nulliparous Sprague Dawley rats - Harishini Rajaratinam; Nur Anissa Vidka Anjani; Wan Ezumi Mohd Fuad (Life Sciences, Medicine and Biomedicine, 2026)
This present study quantified 5-hydroxymethylfurfural (HMF) in ATH samples of different storage durations using UV-visible spectroscopy and evaluated the effects of these samples on the reproductive health of female Sprague Dawley (SD) rats. Rats with regular oestrous cycles were divided into 11 treatment groups (n=10), receiving either distilled water (control), fresh TH (FTH), ATH (24-, 36-, and 48-months old), purified HMF (low, medium, and high doses), or combinations of FTH and HMF. The rats were subsequently administered with test substances via oral gavage on the first day of dioestrus for four consecutive weeks. On the first dioestrus day upon completion of the four-week testing period, the rats (fasted overnight) were anaesthetised followed by blood collection and laparotomy. Blood samples were subjected to biochemical and hormonal analyses, and visceral reproductive organs were collected. The length of the oestrous cycles in control and treatment groups, in both pre (H-statistic=6.50, p=0.77) and during (H-statistic=11.48, p=0.32) treatment period showed no significant differences when evaluated using the Kruskal Wallis test. In addition, the one-way ANOVA test showed no significant differences in the body weights throughout the experimental period (F-statistic=0.195–0.978, p=0.468–0.996). As for the absolute and relative organ weights which were analysed using one-way ANOVA or Kruskal-Wallis analysis, only the absolute (H-statistic=18.87, p=0.042) and relative (H-statistic=20.62, p=0.024) weights of the right fallopian tube showed significant differences. Through the Kruskal-Wallis analysis, significant differences were observed in albumin (H-statistic=22.66, p=0.012), albumin/globulin A/G ratio (H-statistic=20.02, p=0.029), gamma-glutamyl transferase (GGT) (H-statistic=42.41, p